1999
DOI: 10.1159/000007664
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide: A Major Factor for Stress Protein Induction in Reoxygenation Injury in the Intestinal Cell Line Caco-2

Abstract: Background/Aims: Acute intestinal ischemia is followed by cellular destruction and loss of mucosal barrier function. Posthypoxic injury of cellular proteins leads to the synthesis of heat shock proteins. The role of oxygen radicals in this process, however, is not fully established. Methods: In the present study, using the intestinal cell line Caco-2, we investigated the relationship between the synthesis of the heat shock protein HSP70, detected by Western blot and oxygen radicals as well as lactate dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
(30 reference statements)
2
10
0
1
Order By: Relevance
“…Increase in superoxide production and a reduced level of NO are also reported in the postmenopausal state (White et al 2010). Both thee mechanisms are associated with HSP70 induction (Gebhardt et al 1999;Wang et al 1996). Consistent with our presumptions, Molvarec et al (2007bMolvarec et al ( , 2010 demonstrated that serum HSP70 concentrations are decreased in normal human pregnancy, which is associated with down regulation of the immune system.…”
Section: Discussionsupporting
confidence: 84%
“…Increase in superoxide production and a reduced level of NO are also reported in the postmenopausal state (White et al 2010). Both thee mechanisms are associated with HSP70 induction (Gebhardt et al 1999;Wang et al 1996). Consistent with our presumptions, Molvarec et al (2007bMolvarec et al ( , 2010 demonstrated that serum HSP70 concentrations are decreased in normal human pregnancy, which is associated with down regulation of the immune system.…”
Section: Discussionsupporting
confidence: 84%
“…However, excessive production of these ROS may lead to oxidative stress in fish. Over-expression of Hsc70 protects cells from oxidative stress (Dastoor and Dreyer 2000;Gebhardt et al 1999). Up-regulation of Hsc70 gene in A. hydrophila-infected liver and spleen tissues of rohu during 3 to 12 and 3 to 72 hpc, respectively, signifies the protective mechanism of the host cell from infection-related oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting rise in the rates of oxyradical production might increase oxidative stress and thus the need for HSPs for cytoprotection. Previous studies demonstrated the induction of Hsp70 and sHSPs in a number of conditions leading to oxidative stress, including renal ischemia, intestinal hypoxiareoxygenation experiments (Gebhardt et al, 1999;Smoyer et al, 2000) and hypoxia exposure in Lymnaea stagnalis snails (Fei et al, 2007). In the surf clam Donax variabilis, hyperoxia induced the expression of Hsp70, whereas sulfide-induced oxidative damage induced the expression of sHSPs (Joyner-Matos et al, 2006).…”
Section: Hsps and Oxidative Stressmentioning
confidence: 97%